О пилильщиках рода мезонеура - Mesoneura Hartig (Hymenoptera, Tenthredinidae) - Палеоарктики - Ермоленко, В.М. (Вестник зоологии, 1967)
The article deals with the data on ecology and geographical distribution of a representative of Tenthredinidae — Mesoneura lanigera Benson, new for the USSR fauna. The diagnosis of this species is given. The table is presented for the determination of six lcnowrt species of the genus Mesoneura Hartigon the territory of Palearctic.